CRISPRi screens reveal a DNA methylation-mediated 3D genome dependent causal mechanism in prostate cancer - Musaddeque Ahmed (Nature Portfolio, 2021)
Prostate cancer risk-associated SNPs are enriched in noncoding CREs. Here the authors perform CRISPRi screens of CREs in prostate cancer cell lines to describe a causal mechanism synergistically driven by a risk SNP and DNA methylation-mediated 3D genome architecture.